Revisiting the Idealism of Syariah Audit for Islamic Financial Institutions - Mulyany, Ratna; Furqani, Hafas; Ibrahim, Shahul Hameed Mohamed; Hamoudah, Manal Mohammed (al-Uqud : Journal of Islamic Economics, 2021)
The rapid development of syariah audit goes hand in hand with demands for governance of syariah compliance that promotes accountability and transparency. From its inception, syariah audit as a concept has been interpreted and practiced from various perspectives. This research aims to conceptually revisit the ideal conception of syariah audit by looking back at its root, discussing the emergence, meaning, characteristics, and issues of syariah audit. This study demonstrates the need for more holistic development of the conceptual framework for the syariah audit. It consists of defining subject appropriately, standardising the qualification and competence requirements for syariah certified auditors, regulating who should appoint syariah auditors, identifying the scope and extent of syariah audit, establishing the regulatory body forsyariah audit, and enforcing the dedicated standards for syariah audit.Â